Disturbing the bones - Davis, Andrew, 1946-; Biggers, Jeff, 1963- (Melville House, 2024)
Chicago detective Randall Jenkins returns to Cairo, Illinois, where he teams up with ambitious archaeologist Molly Moore to unravel entwined family mysteries and confront a rogue general threatening a global peace summit with a military conspiracy.